Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) bagi Masyarakat Berpenghasilan Rendah (MBR) - khayu rohmi (Journal of Law and Administrative Science, 2023)
Poverty is a phenomenon that is discussed almost throughout the country and is a situation where there is an inability to meet basic needs such as clothing, food, shelter, as well as education and health. This research aims to analyze the implementation of the Self-Help Housing Stimulant Assistance policy as one of the poverty alleviation programs in Indonesia. The research method used is a qualitative method with a literature review approach. The results showed that the Self-Help Housing Stimulant Assistance Program for Low-Income Communities designed by the government in the hope of reducing poverty and overcoming housing backlogs, but the BSPS Program for MBR carried out in Indonesia was only able to overcome poverty but was unable to overcome housing backlogs.